Development of a multinational registry of pediatric deceased organ donation activity. (5th February 2019) - Weiss, Matthew J.; Domínguez‐Gil, Beatriz; Lahaie, Nick; Nakagawa, Thomas A.; Scales, Angie; Hornby, Laura; Green, Meagan; Gelbart, Ben; Hawkins, Kay; Dhanani, Sonny; Dipchand, Anne I.; Shemie, Sam D.; et al.
Abstract: Background: There are no currently agreed upon international standards for reporting of pediatric deceased organ donation activity. This leads to difficulty in comparisons between jurisdictions for both researchers and policy stakeholders. The goal of this project was to develop and test a standardized registry for pediatric deceased donation activity. Methods: Four countries (Canada, Spain, USA, and the UK) with geographical and practice diversity were approached to participate. Iterative exchanges were used to create data fields and definitions that were acceptable to all participants. Data from 2011 to 2015 (inclusive) were requested from national health databases and analyzed on a secure, web‐based survey platform. Results: Data were obtained from three of the four countries (Canada unable to provide). Total pediatric donation rates were stable over the 5‐year period, but with variation between countries. pDCD rates were the most variable, representing 32.2% of total pediatric donation in the UK, 14.4% in the United States, and 2.6% in Spain during the studied period. Most organs from pediatric donors were allocated to adult recipients, though the rates of allocation of pediatric kidneys to pediatric recipients ranged from 7% in the United States to 40% in Spain. Discussion: In this limited cohort of three countries, we demonstrated substantial variation in pediatric donation rates and practice. These data highlight opportunities for practice improvement such as the development of rigorous clinical practice guidelines. Future development of this registry will seek to engage more countries, and address barriers that prevented full participation of approached jurisdictions.